'Letting them loose!' A different approach to a biochemistry post‐exam training session. (16th February 2013) - Flint, Lisa
Abstract This feature looks at changing the format of a well‐established information skills session for first‐year biochemistry students at UCL, to improve its design, delivery and the overall learning experience for the students. After reviewing current literature, active learning methods were explored and an idea of a research‐based quiz based on famous scientists was devised. After a brief introduction to the library resources available, the students were 'let loose' to research their particular scientist and answer a series of questions. Feedback was gained and evaluated and concluded that the session was well received by students. The feature also raises the discussion of generic verses subject‐based information skills training. H.S.